WOLF WARRIOR DIPLOMACY CHINA TERHADAP AMERIKA SERIKAT MELALUI MEDIA SOSIAL DI ERA COVID-19 - Aziz, Aufarrifqi Muthahhari; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The bilateral relationship between the United States and China is peculiar, as they often exhibit hostility but occasionally cooperate for mutual interests, goals, and security. The Covid-19 pandemic has led to conflicts, with President Trump accusing China of being the virus spreader using terms like "China virus" and "kung fu virus". China has adopted the wolf warrior diplomacy strategy. The implementation of this strategy and its outcomes were explored in this study. This research utilized a qualitative approach, analyzing the content of social media and digital propaganda used by China, particularly on platforms like Twitter, during the pandemic period. Public diplomacy and propaganda theories are employed as analytical frameworks. The research showed a shift in China's foreign policy approach, from previously passive to more aggressive and high-profile. China leverages social media to influence international public opinion, shaped a positive narrative regarding its handling of Covid-19, and criticize the United States. The impact is also blatant the positive responses from some segments of American society who agree with the narrative presented by the Chinese government through the video "Once upon a Virus". In other words, this strategy resulted in tension in the dynamics of international relations, geopolitics, deepens the divide, and increases tension, making it difficult to achieve meaningful agreements and cooperation during the Covid-19 pandemic. Keywords: Wolf Warrior Diplomacy, Covid-19, China's Diplomacy Strategy